Flipped classroom with a gamification case method approach for learning statistics - Novia Kuswidayani; Yerry Soepriyanto; Henry Praherdhiono (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Integrating flipped classrooms and gamification in educational statistics aims to enhance student motivation and understanding. This approach actively involves students in case-based learning, immersing them in real or hypothetical problems relevant to the course. This development aims to create an engaging and effective learning model applicable to statistics education. The model development follows five stages: analysis, design, development, implementation, and evaluation. During the flipped class, students review learning materials before the session, allowing in-class time to focus on case-solving discussions and gamification activities. The experiment involved sixth-semester educational technology students taking a statistics education course. Learning design experts validated the model, receiving a positive response (96%), indicating its suitability for implementation. The model's effectiveness was evident in the experiment, with a high success rate of 99%. The design's attractiveness, mainly due to engaging gamification elements, contributed to positive student responses. Research results highlight the success of integrating flipped classrooms with case-based gamification methods, providing an attractive and effective approach to statistics education. AbstrakIntegrasi kelas terbalik dan gamifikasi dalam statistika pendidikan bertujuan meningkatkan motivasi dan pemahaman mahasiswa. Pendekatan ini melibatkan mahasiswa secara aktif dalam pembelajaran berbasis kasus, membenamkan mereka dalam masalah nyata atau hipotesis yang relevan dengan mata kuliah tersebut. Tujuan dari pengembangan ini untuk menciptakan model pembelajaran yang menarik dan efektif untuk diterapkan pada pembelajaran statistik. Pengembangan model melalui lima tahap: analisis, desain, pengembangan, implementasi, dan evaluasi. Selama kelas terbalik, mahasiswa meninjau materi pembelajaran sebelum kelas dimulai, memungkinkan waktu di dalam kelas untuk fokus pada diskusi penyelesaian kasus dan aktivitas gamifikasi. Percobaan melibatkan mahasiswa teknologi pendidikan semester keenam yang mengambil mata kuliah statistik pendidikan. Ahli desain pembelajaran memvalidasi model tersebut, mendapatkan tanggapan positif (96%), menunjukkan kesesuaian untuk diimplementasikan. Efektivitas model terbukti dalam percobaan, dengan tingkat kelulusan tinggi sebesar 99%. Daya tarik desain tersebut dicatat karena elemen gamifikasi yang menarik, berkontribusi pada respon positif dari mahasiswa. Hasil penelitian menyoroti keberhasilan integrasi kelas terbalik dengan metode kasus gamifikasi, memberikan pendekatan yang menarik dan efektif dalam statistika pendidikan.Kata Kunci: Flipped classroom; gamifikasi; keterlibatan pemelajar; pembelajaran berbasis kasus; Statistika